Dilema Tionghoa miskin - Rahoyo, Stefanus (Sleman, Yogyakarta : Tiara Wacana, 2010)
Economic and social conditions of Chinese Indonesian.
Revision of the author's thesis (master's)--Universitas Kristen Satya Wacana, Salatiga.
Includes bibliographical references (p. 179-183).
Keywords: Chinese -- Indonesia -- Economic conditions; Chinese -- Indonesia -- Social conditions